The Influence of Leadership Style and Job Satisfaction on Productivity at PT. Mayora Indah Tbk in West Jakarta - Indrawati, Yuli; Sulaeman, Asep (International Journal of Social Sciences, 2025)
This research aims to determine the influence of leadership style and job satisfaction on employee productivity at PT Mayora Indah Tbk in West Jakarta, both partially and simultaneously. The research used an associative quantitative method with a saturated sampling technique involving 45 respondents. Data analysis includes instrument testing, classical assumption testing, simple linear regression, multiple linear regression, correlation coefficient, coefficient of determination, as well as hypothesis testing via the t test and F test. The results of the analysis show that leadership style partially has a positive effect on employee productivity, with the simple linear regression equation Y = 15.900 + 0.256X1. A correlation coefficient value of 0.465 indicates a strong relationship, and a coefficient of determination of 21.6% indicates that employee productivity is influenced by leadership style by that percentage. The t test produces tcount > ttable (3.638 > 1.301) and is significant at p < 0.05 (0.001 < 0.05), so Ho is rejected and Ha is accepted. Partial job satisfaction also has a positive effect on employee productivity, with the regression equation Y = 15,900 + 0.200X2. A correlation coefficient of 0.281 indicates a moderate relationship, and a coefficient of determination of 7.9% indicates the contribution of the job satisfaction variable to productivity. The t test produces tcount > ttable (2.195 > 1.301) and is significant at p < 0.05 (0.034 < 0.05), so Ho is rejected and Ha is accepted. Simultaneously, leadership style and job satisfaction have a significant effect on employee productivity with the multiple linear regression equation Y = 15.900 + 0.256X1 + 0.200X2 The simultaneous correlation coefficient of 0.607 shows a very strong relationship, with a coefficient of determination of 33.9%. The F test produces Fcount > Ftable (12.273 > 3.22) and is significant at p < 0.05 (0.000 < 0.05), so Ho is rejected and Ha is accepted. This research proves that both leadership style and job satisfaction, partially or simultaneously, have a significant effect on employee productivity.